Données Préliminaires Sur La Carotte M2005-12 Prélevée Au Sommet De L’escarpement Pen Duick (Champ De Volcans De Boue D’el Araich, Maroc) - Adil Chiguer (European Scientific Journal, ESJ, 2017)
The Pen Duick Escarpment is located 30 nautical miles off shore the Moroccan coast in the Gulf of Cadiz and is a fault formed in a compressional system. The area surrounding the escarpment is characterised by a very complex geological. This project aims to study the sedimentological processes on top of the Pen Duick Escarpment and relate them to changes of the last glacial-interglacial period. For this purpose, the sediments were analysed using the X-ray fluorescence (XRF), grain-size distribution and the stable oxygen isotope measurements of planktonic foraminifera. Analysis of the core shows that the core consists mainly of silty clay with foraminifera. Several sandy layers were observed in the core at different depths. In some zones,coral fragments occur, which seem to have been transported to the core site. Stable isotope analysis of planktonic foraminifera shows a repetition of recent Holocene material in the pistoncore. The changes in composition and mineralogy of the sediment in the core might be related to sedimentological processes like currents of strong energy.